Seronegativity and HIV infection. Issue 1 (January 1989) - Lepage, P; Batungwanayo, J; Van de Perre, P
Abstract : An African girl born to an HIV seropositive mother was seropositive during the neonatal period, became seronegative, and was again found to be seropositive at 18 and 20 months of age. We suggest that seronegative children born to seropositive mothers should be followed up for months or even years before HIV infection can be ruled out.